Aṣṭāṅga-yoga dan Upaya Peningkatan Kecerdasan Adversitas Manusia - Dwitayasa, I Made (Jurnal Penelitian Agama Hindu, 2024)
Scientists discovered the paradigm of three human intelligences: intellectual, emotional, and spiritual. This paradigm is known as Intelligence Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ). These three are the most important human intelligences. In addition, adversity intelligence, meaning the ability to face challenges and overcome them, is evolving. This qualitative research focuses on texts to reveal the Hindu concept of intelligence. Research and discussion show that some forms of Hindu intelligence are faith (śradhhā), strength, persistence (vīrya), memory (smṛti), and concentration power (smṛti). The concept of endurance, or resilience, is the nexus of adversity intelligence in both Hindu and Western science. According to the Western perspective, human endurance is linked to the body and mind, making it vulnerable to emptiness. Hinduism thrives on fortitude, divine strength, and readiness to accept failure, happiness, and sorrow with a balanced attitude (Stitaprajña) and ready to fight again. Aṣṭāṅga-yoga can be used to improve adversity intelligence. The more enterprising, diligent, disciplined, and earnest one is, the better the results will be. Adversity intelligence can improve endurance, fighting power, and persistence, interpersonal skills, balance, obedience, and devotion, and a sense of higher purpose in life. Human life as a whole will be affected by these effects.